Engineering the Ionic Self‐Assembly of Polyoxometalates and Facial‐Like Peptides. Issue 44 (13th September 2016) - Li, Jingfang; Li, Xiaodong; Xu, Jing; Wang, Yang; Wu, Lixin; Wang, Yanqiu; Wang, Liyan; Lee, Myongsoo; Li, Wen
Abstract: The self‐assembly behavior of polyoxometalates (PMs) and facial‐like cationic peptides carrying lysine residues were systematically investigated. Circular dichroism and UV/Vis spectra demonstrated that the multivalent electrostatic attractions between polyanionic PMs and short peptides with protonated lysine residues initiated the conformational transition of peptide molecules from random‐coil to β‐sheet state, and subsequently the co‐assembly. TEM and atomic force microscopy (AFM) measurements showed that uniform nanofibers formed with decreasing size of the PMs or increasing the intermolecular forces of the peptides, such as through hydrogen‐bonding, hydrophobic, and/or π–π interactions. Additionally, the stability of the nanostructures can be improved by rational suppression of the electrostatic repulsion of the shell peptides covering the surface of the nanostructures. These results provide new insight into understanding the ionic self‐assembly of peptides and PMs and controlling their final morphology. Abstract : Engineered assembly : The self‐assembly behavior of polyoxometalates and cationic peptides is dependent on the competitive interactions, including hydrogen‐bonds, hydrophobic, π‐π interactions, electrostatic repulsion, and the steric hindrance. These driving forces can be regulated by the subtle alterations of the size of polyoxometalates and/or the residues of peptides, resulting in controllable nanostructures (see scheme).